Municipal Water Supply and Sewage Treatment: Costs, Prices and Distortions (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
Municipal water supply and sewage treatment are essential services that ensure public health and environmental sustainability. However, providing these services involves substantial costs, including water extraction, treatment, distribution, and wastewater treatment. Water pricing and sewage treatment fees play a crucial role in funding these services, but they can lead to distortions, inefficiencies, and equity concerns. This article examines the cost structure of municipal water supply and sewage treatment, the pricing mechanisms, and the potential distortions caused by subsidies, inefficiencies, and market failures. It discusses the various factors that affect pricing, the role of subsidies in making water and sewage services affordable, and the consequences of inefficiencies in service provision. The article concludes by emphasizing the need for a balanced approach to pricing that ensures cost recovery, equity, and efficient resource use.